Cover Page - RIAL-EJ, Editorial (Research and Innovation in Applied Linguistics, 2023)
In response to the need for a scientific forum for research in applied linguistics, vocational English, and English for Specific Purposes (ESP), we are happy to announce that Research and Innovation in Applied Linguistic-Electronic Journal (RIAL-EJ) has successfully published this very first volume and issue. The editors have committed to providing scientific information for the readers, thus helping them understand the current development in the field. In the industrial context, English is a working language for building social interaction and communication with the stakeholders, such as managers, front officers, engineers, IT specialists, etc. Based on the central theme of this issue, â€œDemystifying the Specialized Language Teaching (ESP) and Digital Technologies in Vocational Higher Education,â€ we invite all the practitioners, experts, researchers, and scholars in the field of applied linguistics to contribute to the development of vocational English studies and help the vocational institutions provide ready-work alumni with excellent English language proficiency. The theme aligns with the directorate of vocational educationâ€™s mission, which entails the need to infuse PBL in the curriculum and teaching implementation (Sakarinto, 2020).